Teaching about medicinal plants at school: Following in the footprints of Frei Veloso - Brandão, Maria das Graças Lins; Fonseca, Rômulo dos Santos; Souza, Juliana de Paula; Santos, Aparecida Celia dos; Mencarelli, Fernando Antônio; Scopel, Marina (Seven Editora, 2023)
Brazil is home to the richest, most important and diverse flora in the world. This fact reveals the great plant potential of the country in the development of medicines, cosmetics, nutraceuticals and other innovative products (NEWMAN & CRAGG, 2012). In addition to the vast biodiversity, Brazil also has a rich socio-diversity, built over the centuries by the miscegenation of Amerindian, African and European cultures (VALLI & BOLZANI, 2019). However, despite its recognized potential, native vegetation in Brazil is undergoing an intense process of destruction, caused by a sequence of highly impactful economic cycles, which began with the exploitation of pau-brasil, in the 16th century (DEAN, 1996). Currently, only 7% of the Atlantic Forest is preserved, while other ecosystems such as the Amazon, the cerrados and the caatinga are being rapidly replaced by monocultures of eucalyptus, sugar cane, soy and cattle raising. The consequences of these processes on useful and medicinal native plants are dramatic: a study carried out by the Center Specialized in Aromatic, Medicinal and Toxic Plants Ceplamt/UFMG (supported by FAPEMIG) between 2004-2005, with the population of the mining area of Estrada Real, in Minas Gerais, showed that, even among the elderly inhabitants of rural areas, knowledge about the medicinal applications of native plants was forgotten (BRANDÃO & MONTEMOR, 2008). As a consequence, most of the plants used today as medicines are exotic species, that is, native to other continents, but which have been introduced here since the beginning of Portuguese colonization (FERRÃO, 2004). DOI:https://doi.org/ 10.56238/devopinterscie-156